Right atrial appendage accessory pathway causing pseudo-refractory atrioventricular reentrant tachycardia - Oliveira, Lucas Hollanda; Luize, Christian Moreno; Carvalho, Ricardo Sobral de; Kalil, Felipe; Dietrich, Cristiano de Oliveira; Nogueira, Alleh (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Catheter ablation is the first-line therapy for symptomatic atrioventricular reentrant tachycardia (AVRT). Pseudo-refractory AVRT may stem from misdiagnosis, use of inadequate ablation methods, or the presence of additional concealed or unusual located pathways that initiate or sustain the tachycardia. We present a case of right atrial appendage accessory pathway—a rare and overlooked cause of AVRT—to illustrate the importance of raising suspicion for this condition when standard mapping and ablation around the tricuspid valve annulus fail to eliminate pathway conduction. Furthermore, we present a straightforward, effective approach for localizing the pathway site and safely performing irrigated ablation at the base of the right atrial appendage.